Contributions of geology for the development of ecotourism in the community of Cabeça de Boi, Itambé do Mato Dentro (MG) (Research, Society and Development, 2018)
Ecotourism represents a segment of tourism that uses the natural resources in a sustainable manner, seeking to encourage their conservation and promote the well-being of the population. Thus, this research aimed to characterize, through observation, the lithotypes and geological structures of the natural tourist attractions of the region of Cabeça de Boi, in the municipality of Itambé do Mato Dentro (MG), as well as verifying the existing infrastructure in place for tourist assistance. Thus, the tourist attractions analyzed, represented by Intancado, Chuvisco, Maçã, and Lajeado and Poço waterfalls, are formed by quartzites associated to the Serra do Lobo Unit, Souza-Brumadinho Formation, belonging to the Espinhaço Supergroup. With regard to the infrastructure for tourism service, the negative aspect is the lack of signage to access tourist attractions; on the other hand, we can see the improvement related to the water supply of the community, as well as the capacity of this for the lodging of tourists. In general, aiming to contribute to the development of sustainable tourism in the Cabeça de Boi community, it is necessary to focus on environmental education involving tourists and residents, in order to mitigate negative impacts and preserve the environment.